Tomography of human trabecular bone with a laser-wakefield driven x-ray source. (20th October 2015) - Cole, J M; Wood, J C; Lopes, N C; Poder, K; Abel, R L; Alatabi, S; Bryant, J S J; Jin, A; Kneip, S; Mecseki, K; Parker, S; Symes, D R; et al.
Abstract: A laser-wakefield driven x-ray source is used for the radiography of human bone. The betatron motion of accelerated electrons generates x-rays which are hard (critical energy keV), have small source size (<3 μ m) and high average brightness. The x-rays are generated from a helium gas cell which is near-instantly replenishable, and thus the average photon flux is limited by the repetition rate of the driving laser rather than the breakdown of the x-ray source. A tomograph of a human bone sample was recorded with a resolution down to 50 μ m. The photon flux was sufficiently high that a radiograph could be taken with each laser shot, and the fact that x-ray beams were produced on 97% of shots minimised failed shots and facilitated full micro-computed tomography in a reasonable time scale of several hours, limited only by the laser repetition rate. The x-ray imaging beamline length (not including the laser) is shorter than that of a synchrotron source due to the high accelerating fields and small source size. Hence this interesting laboratory-based source may one day bridge the gap between small microfocus x-ray tubes and large synchrotron facilities.